2015
DOI: 10.1038/pr.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

Urinary neutrophil gelatinase-associated lipocalin: potential biomarker for late-onset sepsis

Abstract: Background:To assess the ability of urinary neutrophil gelatinase-associated lipocalin (UNGAL) to discriminate between culture-positive vs. culture-negative late-onset sepsis evaluations. Methods: This is a prospective observational study of 136 neonates who underwent ≥1 sepsis evaluation at >72 h of age. Urine was obtained at the time of sepsis evaluation to measure UNGAL concentration. Using generalized estimating equations controlling for gender, gestational and postnatal age, acute kidney injury, and withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Sepsis patients have changes in their neuroendocrine system such as activation of sympathetic nervous system, release of vasopressin, and activation of renin -angiotensin -aldosterone system. These changes can result in decrease in renal blood flow, renal tubular epithelial cell necrosis and decline in renal function [13].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis patients have changes in their neuroendocrine system such as activation of sympathetic nervous system, release of vasopressin, and activation of renin -angiotensin -aldosterone system. These changes can result in decrease in renal blood flow, renal tubular epithelial cell necrosis and decline in renal function [13].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is one of the major causes of AKI in neonates. In a study conducted by Pynn et al (18) , urine NGAL was pointed out as a non-invasive biomarker with high negative predictive value at the time of late-onset sepsis assessment in neonates. According to a study conducted by Parravicini et al (4) , on 91 very low birth weight infants, urine NGAL is a promising candidate as an early biomarker for sepsis and it was also shown that urinary NGAL levels was an early biomarker to detect sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no statistically significant difference between the risk factors of sepsis, such as male gender, gestational age below 37 weeks and umbilical cord blood NGAL levels; however, there was a statistically significant difference between PROM, which is also a risk factor in sepsis, and umbilical cord blood NGAL levels. (18) In a group of neonates with intrauterine hypoxia, Essajee et al (20) found that urine NGAL is a predictor of mortality and hypoxic encephalopathy. Similar results were found in another study conducted by Fiala et al (21) .…”
Section: Discussionmentioning
confidence: 99%
“…In children, uNGAL's ability to predict AKI is enhanced when it is used in combination with other biomarkers for renal injury or function such as interleukin-18 (IL-18), Kidney Injury Molecule-1 (KIM-1), and tissue inhibitor of metalloproteinases 1 (TIMP-1) [29,31]. We examined only the association of uNGAL and AKI, as this study was part of a series of studies examining the utility of uNGAL as a biomarker for various outcomes [19,22,43,44]; however, further investigation of the utility of multiple biomarkers in this population is warranted. Finally, while to the best of our knowledge neonates included in our study had normal renal anatomy and function, there may be microscopic changes that could not be appreciated by ultrasound.…”
Section: Strengths and Limitationsmentioning
confidence: 99%